Social movements and the transformation of American health care - Banaszak-Holl, Jane.; Levitsky, Sandra; Zald, Mayer N. (New York ; Oxford : Oxford University Press, 2010)
This is a collection of essays which examine dynamics of change in health care institutions through the lens of contemporary theory and research on collective action. The book conceptualizes the American health care system as being organized around multiple institutions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social medicine -- United States; Social movements -- United States; Medical care -- United States